DOI: 10.11606/t.11.2020.tde-27112020-170944
|View full text |Cite
|
Sign up to set email alerts
|

Implications of pregnant sheep nutrition on progeny\'s myofibers and blood parameters

Abstract: Implications of pregnant sheep nutrition on progeny's myofibers and blood parameters The objective of the work was to evaluate the effect of different energy levels, as well as different energy sources in the diet of the ewes during pregnancy and its impact on growth and metabolism of lambs. Seventy-two ewes were used and randomly distributed in 5 different experimental treatments: diet (CTL) with 100% of the energy recommended by the NRC (2007), low energy (LE) diet with 90% of the recommended energy, or even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…The same was reported by Wilson et al (2016), who fed beef cows in late gestation 100 or 125% energy requirements and observed no effects on the performance or carcass traits of the offspring. In contrast, Oliveira (2020), studying fetal programming using Dorper × Santa Inês ewes fed up to 110% energy requirements, observed that the surplus energy resulted in lambs with the best performance at 60 days of age.…”
Section: Performance Traitsmentioning
confidence: 99%
“…The same was reported by Wilson et al (2016), who fed beef cows in late gestation 100 or 125% energy requirements and observed no effects on the performance or carcass traits of the offspring. In contrast, Oliveira (2020), studying fetal programming using Dorper × Santa Inês ewes fed up to 110% energy requirements, observed that the surplus energy resulted in lambs with the best performance at 60 days of age.…”
Section: Performance Traitsmentioning
confidence: 99%